A tradutibilidade do sentido: o processo de transcrição musical - Victor Melo Vale (2018)
The process of musical transcription has been generally developed as an activity based on and conditioned to the idiomatic universe that it is destined. By privileging the best functioning of the work in the instrument to which the transcription is made, in most cases this transcriptional tradition ends up distorting and reducing the potential expressive structures of the original work, many of them are developed from the relations made between the instrumental idioms and musical speech. The approach with language studies and the theory of translation, especially with Walter Benjamin and Antoine Berman´s thoughts towards the translation phenomenon, where the concept of foreignism recurrently lined and developed in the theorizations of the post Goethe translation philosophers, ends up granting to this activity a more ethical and poetical relation with the original work. The reflection towards concepts such as originality, idioms, fidelity, fruition, authorship, expression, all of them convergent to the similar phenomena of transcription and translation, reconditions and invigorates the debate on the transcriptional activity, which is not based in the possible repertorial adjustments starting from the functionality and mechanicity of the destined instrument, but it is based in the idiomatic-discursive intersections that, potentially establish themselves in the original work and in the attempt of reconstruction of these intersections in the instrument to which it is desired to accomplish the transcription.